Challenges of the current precision medicine approach for pancreatic cancer: A single institution experience between 2013 and 2017. (28th January 2021) - Ding, Ding; Javed, Ammar A.; Cunningham, Dea; Teinor, Jonathan; Wright, Michael; Javed, Zunaira N.; Wilt, Cara; Parish, Lindsay; Hodgin, Mary; Ryan, Amy; Judkins, Carol; McIntyre, Keith; et al.
Abstract: Recent research on genomic profiling of pancreatic ductal adenocarcinoma (PDAC) has identified many potentially actionable alterations. However, the feasibility of using genomic profiling to guide routine clinical decision making for PDAC patients remains unclear. We retrospectively reviewed PDAC patients between October 2013 and December 2017, who underwent treatment at the Johns Hopkins Hospital and had clinical tumor next-generation sequencing (NGS) through commercial resources. Ninety-two patients with 93 tumors tested were included. Forty-eight (52%) patients had potentially curative surgeries. The median time from the tissue available to the NGS testing ordered was 229 days (interquartile range 62–415). A total of three (3%) patients had matched targeted therapies based on genomic profiling results. Genomic profiling guided personalized treatment for PDAC patients is feasible, but the percentage of patients who receive targeted therapy is low. The main challenges are ordering NGS testing early in the clinical course of the disease and the limited evidence of using a targeted approach in these patients. A real-time department level genomic testing ordering system in combination with an evidence-based flagging system for potentially actionable alterations could help address these shortcomings. Highlights: Clinical genomic profiling approach for PDAC patients in routine practice is feasible. Delayed ordering of genomic testing in the clinical course and limited targetable alterations lead to the low percentage of patients who receive matched therapy. A comprehensive real-time platform combining early ordering and potentially actionable alteration identification is urgently needed.